Would nesotriatoma bruneri usinger, 1944 be a valid species? - Alevi, Kaio C.C. [UNESP]; Reis, Yago V. [UNESP]; Guerra, Ana L. [UNESP]; Imperador, Carlos H.L. [UNESP]; Banho, Cecília A. [UNESP]; Moreira, Felipe F.F.; Azeredo-Oliveira, Maria T.V. [UNESP] (Magnolia Press, 2016)
Variation in the size and morphological differences intraspecific of Nesotriatoma flavida led to the description of N. bruneri. However, two years later the same author proposed the synonymization N. bruneri with N. flavida. N. bruneri was revalidated through morphological analysis after 35 years. Thus, given the existing taxonomic questioning between these Cuban triatomines, we analyzed new parameters such as genetic distance from the mitochondrial 16S rDNA deposited in Genbank and cytogenetic characterization, through the constitutive heterochromatin pattern, in order to reassess the specific status of N. bruneri. The analysis of the disposition of constitutive heterochromatin in the genome of these triatomines allowed observing that only the sex chromosome Y is heterochromatic, and the autosomes and the sex chromosomes X are euchromatic. These characteristics are identical to those described for N. flavida. By means of analysis of genetic distance matrix, we found that the genetic distance between N. bruneri and N. flavida was only 0.04%. Thus, by means of extremely low genetic distance and identical cytogenetic characteristics, we suggest that N. bruneri should be back again synonymized with N. flavida. However, we recommend that experimental hybrid crosses and new molecular analysis should be conducted, focusing mainly in the genetic distance based on other genes, on the rate of fertility of eggs and viability of hybrids to confirm the proposed of synonymization.
Keywords: Cytogenetics; Flavida complex; Synonymy